2024
DOI: 10.3390/cryst14010086
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free Double Perovskites: A Review of the Structural, Optoelectronic, Mechanical, and Thermoelectric Properties Derived from First-Principles Calculations, and Materials Design Applicable for Pedagogical Purposes

David O. Obada,
Shittu B. Akinpelu,
Simeon A. Abolade
et al.

Abstract: Metal halide perovskite materials have shown significant advancements in their application as light absorbers in perovskite solar cells, with power conversion efficiencies reaching 27%. However, lead-based perovskites pose a concern due to their toxicity and stability issues in moisture, UV radiation, and heat. This has led to a pressing need to explore substitute materials that do not contain lead but maintain the remarkable characteristics of lead-based perovskites. This review article focuses on halide doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Aligning with the Penn model, Alotaibi et al [77] found that Cs 2 AgBiBr 6 possess a higher static dielectric function than Cs 2 AgBiCl 6 . This suggests that Cs 2 AgBiBr 6 exhibits remarkable optoelectronic properties, as shown and highlighted by a large number of studies [2,[78][79][80][81][82][83][84]. The real dielectric function of both materials exhibit an increase from its static value, reaching a maximum value of 4.29 at 7.04 eV for RbKGeCl 6 and 4.97 at 5.72 eV for RbKGeBr 6 (figure 8(a)), followed by a decrease for higher photon energies with some fluctuations.…”
Section: Optical Propertiesmentioning
confidence: 62%
“…Aligning with the Penn model, Alotaibi et al [77] found that Cs 2 AgBiBr 6 possess a higher static dielectric function than Cs 2 AgBiCl 6 . This suggests that Cs 2 AgBiBr 6 exhibits remarkable optoelectronic properties, as shown and highlighted by a large number of studies [2,[78][79][80][81][82][83][84]. The real dielectric function of both materials exhibit an increase from its static value, reaching a maximum value of 4.29 at 7.04 eV for RbKGeCl 6 and 4.97 at 5.72 eV for RbKGeBr 6 (figure 8(a)), followed by a decrease for higher photon energies with some fluctuations.…”
Section: Optical Propertiesmentioning
confidence: 62%